Improving the tools of clinical pharmacology: Goals for 2017 and beyond. Issue 1 (17th November 2016) - Zineh, I; Abernethy, D; Hop, CECA; Bello, A; McClellan, MB; Daniel, GW; Romine, MH
Abstract : Current trends in pronounced late‐stage attrition rates of promising drug candidates are a pressing concern for patients, providers, and other stakeholders across the health care system. Here, we describe six areas in which clinical pharmacology methods and frameworks can help ameliorate these trends in late‐stage attrition and increase the efficiency of drug development and evaluation. These recommendations are based, in part, on previous stakeholder engagement and input, as well as a previously published white paper.